2020
DOI: 10.1007/s11357-019-00146-3
|View full text |Cite
|
Sign up to set email alerts
|

Metformin and cognition from the perspectives of sex, age, and disease

Abstract: Metformin is the safest and the most widely prescribed first-line therapy for managing hyperglycemia due to different underlying causes, primarily type 2 diabetes mellitus. In addition to its euglycemic properties, metformin has stimulated a wave of clinical trials to investigate benefits on aging-related diseases and longevity. Such an impact on the lifespan extension would undoubtedly expand the therapeutic utility of metformin regardless of glycemic status. However, there is a scarcity of studies evaluating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 151 publications
(163 reference statements)
1
25
0
Order By: Relevance
“…Conversely, it is also suggested that both diseases significantly correlate at early onsets of AD-symptoms [ 115 ]. At present, it is an emerging concern since anti-diabetic Food and Drug Administration approved insulin-sensitive drugs are showing positive effects on dementia risk factors via blocking TXNIP expression downstream associated with inflammatory signaling [ 116 , 117 , 118 ].…”
Section: The Role Of Txnip In Diseasesmentioning
confidence: 99%
“…Conversely, it is also suggested that both diseases significantly correlate at early onsets of AD-symptoms [ 115 ]. At present, it is an emerging concern since anti-diabetic Food and Drug Administration approved insulin-sensitive drugs are showing positive effects on dementia risk factors via blocking TXNIP expression downstream associated with inflammatory signaling [ 116 , 117 , 118 ].…”
Section: The Role Of Txnip In Diseasesmentioning
confidence: 99%
“…Metformin (MET), a drug broadly used for treating type 2 diabetes mellitus (T2DM), has caught considerable attention as a promising anti‐aging drug because of its ability to prolong the lifespan in several species (Chaudhari et al, 2020; Rotermund et al, 2018). MET treatment in early or late middle age also appears attractive because both animal and human studies have implied that dysregulation of insulin function contributes to aging and age‐related neurodegenerative diseases (Craft & Watson, 2004; Verdile et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Sex differences were detected in expression of the organic cation transporter (OCT2), one of the transporters responsible for moving metformin across the cellular membrane. 50 Higher mRNA expression was detected in cortex and hippocampus of female compared to male mice although no sex differences were observed at the protein level. 50 Estrogen lowers the activity of OCT2 in males while testosterone increases OCT2 activity in both males and females in the rat kidney.…”
Section: Discussionmentioning
confidence: 86%